Cadonilimab in combination with chemotherapy for HER2-negative advanced gastric or gastroesophageal junction adenocarcinoma: a cost-effectiveness analysis - Xiang, Zuojuan; Li, Wei; Xia, Qiao (Frontiers in Pharmacology, 2025)
BackgroundThe COMPASSION-15 trial confirmed the safety and effectiveness of cadonilimab, a bispecific antibody targeting both programmed death 1 (PD-1) and cytotoxic T lymphocyte antigen-4 (CTLA-4), in treating human epidermal growth factor receptor 2 (HER2) negative advanced gastric or gastroesophageal junction adenocarcinoma (G/GEJA). Notably, it demonstrated significant survival benefits even in the low programmed death ligand 1 (PD-L1) expression subgroup, overcoming the limitations of current immunotherapy. This study aims to comprehensively evaluate its cost-effectiveness.MethodsThe cost-effectiveness of cadonilimab plus chemotherapy compared to chemotherapy alone was evaluated using a partitioned survival model with a 10-year time horizon, based on data from the COMPASSION-15 trial. Incremental cost-effectiveness ratio (ICER) was estimated to ascertain the cost-effectiveness. Furthermore, subgroup analysis stratified by PD-L1 combined positive score (CPS) thresholds, as well as sensitivity and scenario analyses, were performed.ResultsThe estimated ICER value was $35,613.34/quality-adjusted life-year (QALY) for the entire cohort, $21,142.58/QALY for the high PD-L1 expression subgroup (CPS ≥5), and $45,000.62/QALY for the low PD-L1 expression subgroup (CPS <5). Only the high PD-L1 expression subgroup achieved the cost-effectiveness, as its ICER value was below the willingness-to-pay (WTP) threshold of $24,600/QALY. Sensitivity and scenario analyses demonstrated the robustness of the result.ConclusionIn China, incorporating cadonilimab with chemotherapy was found to be more cost-effective as a first-line treatment for HER2-negative advanced G/GEJA in the PD-L1 CPS ≥5 subgroup. Nevertheless, it was not cost-effective for either the entire cohort or the PD-L1 CPS <5 subgroup. These findings can provide valuable insights for future pricing strategies and healthcare decision-making.